Konsep Pendidikan Karakter Perspektif Thomas Lickona dan Ki Hajar Dewantara - Dyan Nur Hikmasari; Happy Susanto; Aldo Redho Syam (Universitas Muhammadiyah Ponorogo, 2021)
The purpose of the study was to determine the concept of character education according to Thomas Lickona and Ki Hadjar Dewantara. Which later is expected to be able to describe in more detail the concept of character education according to Thomas Lickona and Ki Hadjar Dewantara. This research is library research, so all the data presented is obtained from tracing primary sources, namely the translated book of Thomas Lickona Educating for Character and Ki Hadjar Dewantara's Character Education book, as well as various other supporting sources. With this descriptive, analytical, and comparative search, it is hoped that it will be able to examine the concept of character education according to Thomas Lickona and Ki Hadjar Dewantara. The results of this study found that the concept of character education of Thomas Lickona and Ki Hajar Dewantara is how all social elements have a strong role in the process of forming one's character, both in the age group, professional group and so on, as well as in developing character and values which are a target or achievement. in the educational process at school.